Platelet factor 4 release in patients undergoing cardiopulmonary resuscitation: can reperfusion be impaired by platelet activation? - Böttiger, Bernd W.; Böhrer, Hubert; Böker-Blum, Thomas; Motsch, Johann; Aulmann, Michael; Martin, Eike (Acta anaesthesiologica Scandinavica, 1996)
Background: Reperfusion following cardiac arrest is associated with a marked activation of blood coagulation. This seems to be associated with microcirculatory reperfusion disorders. The present study was designed to investigate the possible involvement of platelets in reperfusion injury following cardiac arrest. Plasma levels of platelet factor 4 (PF 4) were used as an indicator for in vivo platelet activation because PF 4 is known to be released from platelets during aggregation. Methods: Plasma PF 4 levels (normal range: < 5 IU/mL) were measured in 18 patients at predetermined time points during cardiopulmonary resuscitation (CPR). In the case of restoration of spontaneous circulation, additional blood samples were analyzed until seven days after stabilization. The PF 4 levels of four sex-matched volunteers were used as controls. Results: The median of the maximum individual PF 4 levels measured during CPR was 27.5 IU/mL (range 1.2 to 90 IU/mL; P < 0.01 versus controls). Compared with PF 4 levels in control volunteers (median: 0.35 IU/mL; range 0.2 to 0.6 IU/mL), PF 4 levels were significantly elevated in patients during CPR and in the early phase until 24 hours after restoration of spontaneous circulation (P < 0.05). Conclusion: A marked increase in PF 4 levels was observed during CPR and in the early phase after cardiac arrest in man. This increase in PF 4 levels has to be viewed as an indicator of platelet activation, which may play a role in the etiology of reperfusion injury and microcirculatory reperfusion disorders occurring after cardiac arrest.
Gesehen am 02.04.2024